How action selection can be embodied: intracranial gamma band recording shows response competition during the Eriksen flankers test - Caruana, Fausto; Uithol, Sebo; Cantalupo, Gaetano; Sartori, Ivana; Lo Russo, Giorgio; Avanzini, Pietro (Frontiers in Human Neuroscience, 2014)
Recent findings in monkeys suggest that action selection is based on a competition between various action options that are automatically planned by the motor system. Here we discuss data from intracranial EEG recordings in human premotor cortex during a bimanual version of the Eriksen flankers test that suggest that the same principles apply to human action decisions. Recording sites in the dorsal premotor cortex show an early but undifferentiated activation, a delayed response that depends on the experimental conditions and, finally, a movement related activation during action execution. Additionally, we found that the medial part of the premotor cortex show a significant increase in response for ipsilateral trials, suggesting a role in inhibiting the wrong response. The ventral premotor cortex seems to be involved in action execution, rather than action selection. Together these findings suggest that the human premotor cortex is part of a network that specifies, selects, and executes actions.